Higher risk of complications in odynophagia-associated dysphagia in amyotrophic lateral sclerosis - Karen Fontes Luchesi; Satoshi Kitamura; Lucia Figueiredo Mourão (Arquivos de Neuro-Psiquiatria)
Objective This investigation aimed to identify associated factors with dysphagia severity in amyotrophic lateral sclerosis (ALS). Method We performed a cross-sectional study of 49 patients with ALS. All patients underwent fiberoptic endoscopy evaluation of swallowing and answered a verbal questionnaire about swallowing complaints. The patients were divided into groups according to dysphagia severity. Results Among the factors analyzed, only odynophagia was associated with moderate or severe dysphagia. Conclusion Odynophagia was associated with moderate and severe dysphagia in ALS and suggests a high risk of pulmonary and nutritional complications.